Blood biomarker panel recommended for personalized prediction, prognosis, and prevention of complications associated with abdominal aortic aneurysm - Molacek, Jiri; Treska, Vladislav; Zeithaml, Jan; Hollan, Ivana; Topolcan, Ondrej; Pecen, Ladislav; Slouka, David; Karlikova, Marie; Kucera, Radek (The EPMA journal, 2019)
The aim of the study was to evaluate the ability of following biomarkers as diagnostic tools and risk predictors of AAA: C-reactive protein, interleukin-6, pentraxin-3, galectin-3, procollagen type III N-terminal peptide, C-terminal telopeptide of type I collagen, high-sensitive troponin I, and brain natriuretic peptide. Seventy-two patients with an AAA and 100 healthy individuals were enrolled into the study. We assessed individual biomarker performance and correlation between the AAA diameter and biomarker levels, and also, a multivariate logistic regression was used to design a possible predictive model of AAA growth and rupture risk. We identified following four parameters with the highest potential to find a useful place in AAA diagnostics: galectin-3, pentraxin-3, interleukin-6, and C-terminal telopeptide of type I. The best biomarkers in our evaluation (galectin-3 and pentraxin-3) were AAA diameter-independent. With the high AUC and AAA diameter correlation, the high-sensitive troponin I can be used as an independent prognostic biomarker of the upcoming heart complications in AAA patients. Authors recommend to add biomarkers as additional parameters to the current AAA patient management. Main addition value of biomarkers is in the assessment of the AAA with the smaller diameter. Elevated biomarkers can change the treatment decision, which would be done only based on AAA diameter size. The best way how to manage the AAA patients is to create a reliable predictive model of AAA growth and rupture risk. A created multiparameter model gives very promising results with the significantly higher efficiency compared with the use of the individual biomarkers.
Keywords: Brain natriuretic peptide; Biomarker panel; C-Terminal telopeptide of type I collagen; Galectin-3; Pentraxin-3; Multivariate model; High-sensitive troponin I; Interleukin-6; Procollagen type III N-terminal peptide; Abdominal aortic aneurism; Patient stratification; Predictive preventive personalized medicine; Multivariate stepwise logistic regression